Leonurine ameliorates experimental type 2 diabetes through gut microbiota remodeling, enhanced butyrate production, and MPC2 activation to restore GLP-1 secretion - Zhang, Yaoyuan; Chen, Wanyi; Yu, Xinyuan; Feng, Jianhua; Sammad, Abdul; Wang, Zhenbo; Yin, Kai (Frontiers in Pharmacology, 2026)
The core pathophysiological mechanism of type 2 diabetes mellitus (T2DM) is closely associated with gut microbiota dysbiosis and its consequential impairment of enteroendocrine glucagon-like peptide-1 (GLP-1) secretion. T2DM mouse model was established using high-fat diet (HFD) feeding combined with streptozotocin (STZ) administration. Diabetic mice received 30 or 60 mg/kg of leonurine (LEO) via daily gavage for 12 weeks. Gut microbiota composition was profiled by metagenomic sequencing, fecal short chain fatty acids (SCFAs) concentrations were quantified via enzyme-linked immunosorbent assay (ELISA), and GLP-1 expression was assessed using oral glucose tolerance tests (OGTT), ELISA, and immunofluorescence. In vitro, high-glucose (25 mM)-challenged GLUTag enteroendocrine cells were employed to delineate the butyrate–mitochondrial pyruvate carrier 2 (MPC2) regulatory network using qPCR and Western blotting. LEO intervention significantly ameliorated glucose intolerance in diabetic mice and elevated GLP-1 levels in serum and colonic tissues. Metagenomic analysis revealed that LEO (60 mg/kg) remodeled gut microbiota structure, markedly enhancing α-diversity and specifically enriching butyrate-producing Alistipes. Mechanistically, butyrate activated MPC2 expression, effectively restoring cristae architecture defects observed by transmission electron microscopy, thereby promoting GLP-1 secretion. Crucially, MPC2 knockdown abrogated the secretagogue effect of butyrate on GLP-1 in GLUTag cells. LEO alleviates T2DM by remodeling the gut microbiota ecosystem, enhancing butyrate biosynthesis, and activating an MPC2-dependent mitochondrial energy metabolism pathway to reverse GLP-1 secretory dysfunction in intestinal L cells. This study establishes MPC2-mediated mitochondrial functional repair as a core mechanism through which microbial metabolites regulate enteroendocrine hormone secretion, identifying a novel therapeutic target within the “gut–islet axis” for diabetes intervention. Future studies should identify its active constituents, elucidate downstream effectors, and validate this mechanism in germ-free models.